2000
DOI: 10.1143/jjap.39.l1161
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Recording on Magneto-Optical Media Using Merge Type Giant Magneto-Resistive Head

Abstract: TbFeCo media for perpendicular magnetic recording were developed by employing a NiP underlayer that controls the magnetic properties of a TbFeCo magnetic layer. Dynamic write-read characteristics were examined using a conventional merge-type giant magneto-resistive (GMR) head originally designed for longitudinal magnetic recording. A clear magnetic transition of 450 kFCI (kilo Flux Change per Inch), a high media signal-to-noise ratio (SNR), and acceptable overwrite properties were obtained by optimizing the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Referring to the previous studies on the Sm-Co permanent magnets (24)(25)(26)(27)(28)(29), we consider that the Cu atoms around the interface stabilize the SmCo 5 phase and promote its crystallization. In other words, the Cu layer is conjectured to be useful in respect of the formation of a Sm-Co-Cu intermetallic compound, i.e., Sm(Co,Cu) 5 . An X-ray diffractometry indicated that the Cu atoms were substitutionally dissolved in the Co sites of SmCo 5 and Sm(Co,Cu) 5 was formed (21).…”
Section: Microstructural Analysesmentioning
confidence: 99%
“…Referring to the previous studies on the Sm-Co permanent magnets (24)(25)(26)(27)(28)(29), we consider that the Cu atoms around the interface stabilize the SmCo 5 phase and promote its crystallization. In other words, the Cu layer is conjectured to be useful in respect of the formation of a Sm-Co-Cu intermetallic compound, i.e., Sm(Co,Cu) 5 . An X-ray diffractometry indicated that the Cu atoms were substitutionally dissolved in the Co sites of SmCo 5 and Sm(Co,Cu) 5 was formed (21).…”
Section: Microstructural Analysesmentioning
confidence: 99%
“…Recent studies have shown that an underlayer with a grainlike structure provides high recording density in a TbFeCo magnetic recording medium. [4][5][6] This behavior is attributed to the grainlike structure introducing pinning sites for restricting the domain wall displacements of recorded bits. Some of the authors of this paper have been studying Al film as the underlayer for the TbFeCo recording layer and reported that its recording density is markedly improved both in the thermally assisted and even in a nonassisted, conventional magnetic recording method.…”
Section: Introductionmentioning
confidence: 97%
“…This is because the TbFeCo recording layer has strong exchange coupling and shows an amorphous nature with no magnetic borders. 4,5) Therefore, it is difficult to record small magnetic domains if the underlayer is not used. In contrast, with only 4 nm of Al underlayer, the grainlike structure introduces pinning sites and domain wall movement is limited, resulting in the stable existence of small magnetic domains, and the linear recording density is improved.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic properties of TbFeCo films such as Curie temperature (T c ), magnetic anisotropy energy (K u ), and saturation magnetization (M s ) can be suitably designed for the perpendicular magnetic recording medium application [1][2][3]. In these referenced papers, TbFeCo alloy film compositions were adjusted to provide read-back signal at the room temperature, therefore the alloy compositions were far off from the room temperature compensation composition.…”
Section: Introductionmentioning
confidence: 99%